2021
DOI: 10.1182/blood.2020008503
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced homology-directed repair for highly efficient gene editing in hematopoietic stem/progenitor cells

Abstract: Lentivector gene therapy for X-linked chronic granulomatous disease (X-CGD) has proven to be a viable approach, but random vector integration and subnormal protein production from exogenous promoters in transduced cells remain concerning for long-term safety and efficacy. A previous genome editing-based approach using SpCas9 and an oligodeoxynucleotide donor to repair genetic mutations demonstrated the capability to restore physiological protein expression, but lacked sufficient efficiency in quiescent CD34+ h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 31 publications
(53 reference statements)
6
56
0
Order By: Relevance
“…In developing protocols for genome editing of hematopoietic cells, significant effort has been expended on the targeted nuclease: developing platforms for efficient transient delivery, 2 , 4 , 21 , 22 optimizing protein sequences, 23 and chemically modifying RNA components 24 to maximize on-target nuclease activity while minimizing potentially deleterious off-target DNA break formation. Additional improvements in HSPC genome editing have focused on identifying culture conditions that facilitate HDR through the manipulation of the cell cycle or DNA repair pathways, 21 , 25 , 26 as well as to retain optimal stemness and proliferative potential after engraftment. 8 , 11 , 12 , 21 , 27 In contrast, less attention has been paid to conditions that could affect the delivery of the homology donor DNA using AAV vectors.…”
Section: Introductionmentioning
confidence: 99%
“…In developing protocols for genome editing of hematopoietic cells, significant effort has been expended on the targeted nuclease: developing platforms for efficient transient delivery, 2 , 4 , 21 , 22 optimizing protein sequences, 23 and chemically modifying RNA components 24 to maximize on-target nuclease activity while minimizing potentially deleterious off-target DNA break formation. Additional improvements in HSPC genome editing have focused on identifying culture conditions that facilitate HDR through the manipulation of the cell cycle or DNA repair pathways, 21 , 25 , 26 as well as to retain optimal stemness and proliferative potential after engraftment. 8 , 11 , 12 , 21 , 27 In contrast, less attention has been paid to conditions that could affect the delivery of the homology donor DNA using AAV vectors.…”
Section: Introductionmentioning
confidence: 99%
“…41,42 In the same direction, 53BP1 inhibition facilitates HDR in human HSPCs. 43,44 Other groups have reported the use of SR-1 molecule as an HDR pathway enhancer in TALEN and CRISPR/Cas9-mediated editing systems. 45 Aside from small molecules, it has been recently reported that inhibition of p53 increases the rate of HDR.…”
Section: Discussionmentioning
confidence: 99%
“…HDR-mediated genome editing requires the supply of a DNA donor template, harboring homologous sequences with the nuclease target site, and may be exploited for the following applications: (i) targeted correction of point mutations : delivery of a nuclease that cleaves close to the mutation site and of a donor template containing the wild-type sequence (Urnov et al, 2005 ) can be exploited to correct single nucleotide mutations. This approach may be suitable for SCD, which is caused by a single amino acid substitution (Glu to Val) in the sixth position of the HBB gene (Dever et al, 2016 ; DeWitt et al, 2016 ; Park et al, 2019 ; Pattabhi et al, 2019 ; Romero et al, 2019 ), and for X-linked chronic granulomatous disease (CGD), often caused by mutations in the CYBB gene (De Ravin et al, 2017 , 2021 ); (ii) in situ gene correction by targeted insertion of a cDNA : many monogenetic diseases are not caused by a recurrent single nucleotide mutation, but rather different mutations affecting the same gene. Integration of a functional cDNA, spanning the mutation hotspots, in the intended region of the target gene (e.g., endogenous start codon, intronic region), can simultaneously bypass all downstream mutations (Voit et al, 2014 ).…”
Section: Therapeutic Opportunities For Targeted Genome Editing In Hspcsmentioning
confidence: 99%
“…In vitro transcribed mRNA encoding for the nucleases (Genovese et al, 2014 ; Wang et al, 2015 ; Schiroli et al, 2017 ) or ribonucleoprotein (RNP) assembled with recombinant Cas protein and sgRNA (Hendel et al, 2015 ; Dever et al, 2016 ) have become the gold standard to achieve a high but transient nuclease activity in HSPCs and other target cells (Hubbard et al, 2016 ; Eyquem et al, 2017 ). Transduction with viral vectors as integrase-defective LVs (IDLVs) or adeno-associated vectors serotype 6 (AAV6) (Genovese et al, 2014 ; Wang et al, 2015 ; Dever et al, 2016 ; Schiroli et al, 2017 ; Kuo et al, 2018 ; Pavel-Dinu et al, 2019 ; Rai et al, 2020 ), as well as the electroporation of single-stranded phosphorothioate-modified oligodeoxynucleotides (ssODNs) (DeWitt et al, 2016 ; De Ravin et al, 2017 , 2021 ; Park et al, 2019 ; Pattabhi et al, 2019 ; Romero et al, 2019 ), are the vehicles currently preferred to deliver the DNA template for HDR in HSPCs. Overall, these platforms offer a broad spectrum of cargo capacities and may be suitable for different editing strategies.…”
Section: Challenges and Advances Toward Clinical Application Of Hspc Gene Editingmentioning
confidence: 99%
See 1 more Smart Citation